Exposure method and structure of quartz substrate film lithium niobate material
By coating electron beam negative glue and metal aluminum on the surface of the quartz-based thin film lithium niobate material, and using electron beam exposure and development technology, the problem of poor transparency and conductivity of the material is solved, and a high-precision exposure and high bandwidth thin film lithium niobate modulator is achieved.
Patent Information
- Application Number
- CN202311160026.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, the transparency and conductivity of the quartz-based thin film lithium niobate material is poor, which makes it difficult for electron beam exposure machines to calibrate and introduces severe splicing gaps.
The surface of the thin film lithium niobate material is coated with electron beam negative glue HSQ, and the metal aluminum film is evaporated thereon to enhance the conductivity. Then, an electron beam exposure machine was used to expose the fine micro-nano pattern and developed with tetramethylammonium hydroxide developer. Finally, the metal aluminum was removed by corrosion by TMAH developer, and HSQ was converted to SiO2 as a masking layer.
The conductivity is improved, the splicing gap is reduced, the complex metal etching process is avoided, and the exposure method of high-bandwidth thin-film lithium niobate modulators is realized.
Smart Images

Figure CN119575753A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thin-film lithium niobate, and more specifically, relates to an exposure method and structure of a quartz substrate thin-film lithium niobate material. Background Art
[0002] Lithium niobate (LiNbO3) is a compound of niobium, lithium and oxygen. Lithium niobate crystals have many photoelectric effects, strong controllable performance, stable physical and chemical properties, and a wide range of light transmission. In optical devices based on bulk lithium niobate crystals, light is confined in a planar waveguide formed by ion diffusion or proton exchange. The refractive index difference is usually small, and the device size is relatively large, which makes it difficult to meet the needs of miniaturization and integration of optical devices. Thin-film lithium niobate is produced by peeling off a lithium niobate thin film from a bulk lithium niobate crystal through "ion slicing" and bonding it to a Si wafer or quartz substrate with a SiO2 buffer layer to form a thin-film lithium niobate bulk material. Compared with traditional bulk material structures, thin-film lithium niobate structures can achieve ultrafast electro-optical effects and highly integrated optical waveguides, and have excellent characteristics such as large bandwidth, low power consumption, low loss, and small size. They can also be manufactured on a large wafer scale, making them ideal electro-optic modulator materials. The higher dielectric constant of lithium niobate bulk material makes the refractive index of microwave signals much larger than the refractive index of light waves (i.e., refractive index mismatch) and the characteristic impedance of the traveling wave electrode much smaller than the characteristic impedance of the terminal load (i.e., impedance mismatch), resulting in a decrease in the operating bandwidth of the lithium niobate electro-optic modulator. Compared with silicon-based substrates, the use of low-dielectric-constant quartz material as the base wafer of lithium niobate single crystal thin films can achieve a good match between the microwave refractive index and the light wave refractive index, thereby improving the modulation bandwidth.
[0003] The structure of the thin-film lithium niobate material (LNOI) discussed in the present invention is a quartz substrate with a layer of SiO2 on it and a thin-film lithium niobate on the surface. The bulk material structure is transparent and has poor conductivity. Transparent materials cannot be used for laser ranging, which affects the calibration of electron beam lithography (EBL) and introduces serious splicing gaps.
[0004] In view of this, how to overcome the technical problems existing in the above-mentioned prior art is a difficult problem to be solved urgently in this technical field. Summary of the invention
[0005] One of the purposes of the present invention is to overcome the technical problems existing in the above-mentioned prior art, and to propose an exposure method and structure for a quartz substrate thin film lithium niobate material, which overcomes the technical bottleneck of EBL which is difficult to expose transparent materials, improves the graphic accuracy of materials with poor conductivity after exposure and development, reduces the splicing gap, avoids the complex metal etching process, and produces a high-bandwidth thin film lithium niobate modulator.
[0006] To achieve the above-mentioned object, the first aspect of the present invention provides an exposure method for a quartz substrate thin film lithium niobate body material, comprising:
[0007] Coating a layer of electron beam negative resist on the thin film lithium niobate body material;
[0008] Evaporate a metal aluminum film on the electron beam negative resist;
[0009] The micro-nano fine pattern was exposed by electron beam exposure machine and developed by tetramethylammonium hydroxide developer.
[0010] In an optional embodiment, the thin film lithium niobate body material comprises a quartz layer, a silicon dioxide layer and a lithium niobate thin film layer; wherein:
[0011] The quartz layer serves as a substrate;
[0012] The silicon dioxide layer is located on the quartz layer;
[0013] The lithium niobate thin film layer is located on the silicon dioxide layer.
[0014] In an optional embodiment, the thickness of the quartz layer is 550±100 um; the thickness of the silicon dioxide layer is 2±0.5 um; and the thickness of the lithium niobate thin film layer is 550±150 nm.
[0015] In an optional embodiment, the electron beam negative resist includes HSQ, and the thickness of the electron beam negative resist is 700±200 nm.
[0016] In an optional embodiment, the metal aluminum film has a thickness of 15-50 nm.
[0017] In an optional implementation, the electron beam exposure machine uses a high voltage of 100 kV; the concentration of the tetramethylammonium hydroxide developer is 20%±10%.
[0018] In an optional embodiment, coating a layer of electron beam negative resist on the thin film lithium niobate material specifically includes:
[0019] Electron beam negative photoresist HSQ was applied to 2-inch to 4-inch thin film lithium niobate material. The rotation speed of the photoresist was 2500±500 rpm and the photoresist thickness was controlled at 700±200nm.
[0020] In an optional embodiment, evaporating a metal aluminum film on the electron beam negative resist specifically includes:
[0021] A 15-50nm thick metal aluminum film is evaporated on the surface of the lithium niobate thin film material after the coating by an evaporator.
[0022] In an optional embodiment, the exposing of micro-nano fine patterns using an electron beam exposure machine and developing with a tetramethylammonium hydroxide developer specifically includes:
[0023] 100kV electron beam exposure was used, and the exposure resolution was 0.1 nanometer;
[0024] A 20%±10% concentration of tetramethylammonium hydroxide developer is used, and development is performed for 40±5 seconds by combining low-speed static development with high-speed dynamic spray development.
[0025] The second aspect of the present invention provides an exposure structure of a quartz substrate thin film lithium niobate material, which includes, from bottom to top, a quartz layer, a silicon dioxide layer, a lithium niobate thin film layer, an electron beam negative photoresist layer and a metal aluminum thin film layer, an electron beam exposure area is arranged on the metal aluminum thin film layer, and the structure after exposure by an electron beam exposure machine and development with a tetramethylammonium hydroxide developer includes, from bottom to top, a quartz layer, a silicon dioxide layer, a lithium niobate thin film layer, and a silicon dioxide masking layer, and the range of the silicon dioxide masking layer is the same as the range of the electron beam exposure area.
[0026] In general, the above technical scheme conceived by the present invention has the following beneficial effects compared with the prior art: the structure of the thin-film lithium niobate material (LNOI) of the present invention is a quartz substrate, on which is a layer of SiO2, and the surface is a thin-film lithium niobate. The bulk material structure is transparent and has poor conductivity. The transparent material cannot be laser-measured, which affects the EBL calibration and introduces serious splicing gaps. In response to this problem, the present invention first coats a layer of electron beam photoresist negative photoresist HSQ on the surface of the bulk material, and then evaporates a layer of metal aluminum thereon. After the metal is evaporated, the transparency is weakened and white appears, and the EBL can be laser-measured and calibrated. Then, an electron beam exposure machine (EBL) is used to expose micro-nano fine patterns, and tetramethylammonium hydroxide (TMAH) developer is used for development. The metal aluminum film can enhance the conductivity on the LNOI surface to improve the exposure accuracy and effect, and TMAH can corrode and remove the aluminum film during the development process, and convert HSQ into SiO2 as a masking layer for subsequent etching processes. The present invention overcomes the technical difficulty that transparent materials and materials with poor conductivity are not easily exposed by EBL, avoids the complex process of metal etching, and provides an exposure method for a thin-film lithium niobate modulator with a higher bandwidth. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A flow chart of an exposure method for a quartz substrate thin film lithium niobate material provided in Example 1 of the present invention;
[0028] Figure 2 A detailed flow chart of the exposure method of the quartz substrate thin film lithium niobate body material provided in Example 2 of the present invention;
[0029] Figure 3A schematic diagram of the structure of a thin-film lithium niobate material provided in Example 2 of the present invention;
[0030] Figure 4 A schematic diagram of a structure to be exposed by EBL provided in Embodiment 2 of the present invention;
[0031] Figure 5 A schematic diagram of EBL exposure provided in Example 2 of the present invention;
[0032] Figure 6 This is a schematic diagram of the wafer surface structure after development with the TMAH solution provided in Example 2 of the present invention. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] The present invention is an architecture of a specific functional system, so the specific embodiments mainly illustrate the functional logical relationship between the various structural modules, and do not limit the specific software and hardware implementation methods.
[0035] In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other, and the order of each step can be changed if it is logical and does not conflict. The present invention will be described in detail below with reference to the accompanying drawings and embodiments.
[0036] Electron beam exposure technology is a micro-machining technology that uses electron beams to irradiate electronic resists and produce patterns in resists after development. The accuracy of electron beam exposure can reach the nanometer level. The commonly used electron beam negative photoresist is HSQ. HSQ photoresist forms amorphous SiO2 under electron beam exposure and development. It has good plasma etching resistance and excellent resolution, but it is more likely to show write field splicing errors than positive photoresists. The electron beam exposure pattern structure can be regarded as a combination of multiple write fields. During each write field exposure, the electron beam exposure machine will use a laser to measure the height of the sample from the lens and the collimation system will adjust the electron beam deflection to improve the consistency of the write field area and reduce the splicing gap. Due to the need for reflected signals, lasers cannot measure transparent materials or the measurement is erroneous, which will affect the calibration accuracy and exposure effect. In addition, materials with poor conductivity cannot conduct the electrons that reach the surface, and electron stacking will form electromagnetic field interference on the material surface, resulting in subsequent electron beam exposure. Astigmatism, defocusing, and severe splicing gaps are introduced. TMAH is a strong alkaline solution, which can not only make HSQ form amorphous SiO2 after exposure, but also quickly corrode metal Al.
[0037] Through the above characteristics, an embodiment of the present invention provides an exposure method for a quartz substrate thin film lithium niobate body material. First, a layer of electron beam photoresist negative photoresist HSQ is coated on the surface of the body material, and then a layer of metal aluminum is evaporated thereon. After the metal is evaporated, the transparency is reduced and it appears white. The EBL can be calibrated by laser ranging. Then, an electron beam exposure machine (EBL) is used to expose micro-nano fine graphics, and tetramethylammonium hydroxide (TMAH) developer is used for development. The metal aluminum film can enhance the conductivity on the LNOI surface and improve the exposure accuracy and effect, and TMAH can corrode and remove the aluminum film during the development process, and convert HSQ into SiO2 as a masking layer for subsequent etching processes. The present invention overcomes the technical difficulties that EBL is not easy to expose transparent materials and materials with poor conductivity, and avoids the complex process of metal etching.
[0038] Embodiment 1:
[0039] like Figure 1 As shown, the present invention provides an exposure method for a quartz substrate thin film lithium niobate material, comprising the following steps.
[0040] Step 101: Coat a layer of electron beam negative photoresist on the thin-film lithium niobate body material. In an optional implementation of the preferred embodiment, the thin-film lithium niobate body material includes a quartz layer, a silicon dioxide layer and a lithium niobate thin film layer; wherein: the quartz layer serves as a substrate; the silicon dioxide layer is located on the quartz layer; the lithium niobate thin film layer is located on the silicon dioxide layer. In an optional implementation of the preferred embodiment, the thickness of the quartz layer is 550±100um; the thickness of the silicon dioxide layer is 2±0.5um; the thickness of the lithium niobate thin film layer is 550±150nm. In specific implementation, coating a layer of electron beam negative photoresist on the thin-film lithium niobate body material specifically includes: performing electron beam negative photoresist HSQ coating on a 4-inch thin-film lithium niobate body material, the coating machine speed is 2500 rpm, and the photoresist thickness is controlled at 700±200nm.
[0041] Step 102: Evaporate a metal aluminum film on the electron beam negative photoresist. In an optional implementation of the preferred embodiment, the electron beam negative photoresist includes HSQ, and the thickness of the electron beam negative photoresist is 700±200nm. In an optional implementation of the preferred embodiment, the thickness of the metal aluminum film is 15-50nm. HSQ is an ultra-high resolution electron beam negative photoresist, which is composed of hydrogen silsesquioxane (HSQ) resin in a methylisobutylketone (MIBK) solvent, which we usually refer to as HSQ. As an inorganic material, HSQ has good plasma corrosion resistance and selectivity for silicon. It also has excellent resolution. However, HSQ requires a high dose, resulting in a long write time, and some inconsistencies and abnormal behaviors may occur. It is more likely to show write field splicing errors than positive photoresist. Since HSQ glue forms amorphous SiO2 under the action of electron beam or X-ray irradiation energy, it exhibits a series of excellent properties: higher resolution (<10nm), it is reported that 6nm isolated structure with good line edge roughness can be obtained at 20nm glue thickness, high mechanical stability and etching resistance, not easy to deform under scanning electron microscope, which is helpful for the observation and measurement of fine structure. This glue also has certain disadvantages when exposed under high voltage system: low sensitivity, high exposure dose, long exposure time, higher requirements for equipment stability, especially high voltage system (100kV), more obvious proximity effect of dense structure, reduced steepness of graphic side wall, organic solvent cannot be used for glue removal due to the formation of amorphous SiO2 after exposure, BHF is required for glue removal, there are restrictions on some substrate materials, short warranty period, this glue has a warranty period of only 6 months, and the product received by customers often has a shorter warranty period, and the storage conditions are harsh (5℃). HSQ has other characteristics, for example: when the electron beam deposition energy reaches a certain amount during the electron beam exposure process, HSQ can break the Si-H and Si-O bonds in the box-shaped unit, thereby forming a three-dimensional network structure, which can significantly reduce the dissolution rate of HSQ in the developer. The pre-baking process also promotes the transformation of HSQ from a box-shaped structure to a network structure, thereby improving the sensitivity. Of course, the contrast will also decrease. High-concentration TMAH developer produces a greater development speed for box-shaped HSQ, which means a decrease in sensitivity, an increase in contrast, and an easy acquisition of a high aspect ratio structure with steep side walls. In specific implementation, the sputtering of a layer of metal aluminum film on the electron beam negative photoresist specifically includes: using a sputtering machine to sputter a layer of 15-50nm metal aluminum film on the surface of the thin film lithium niobate body material after uniform coating.
[0042] Step 103: Expose the micro-nano fine pattern using an electron beam exposure machine, and develop it with a tetramethylammonium hydroxide developer. In an optional implementation of the preferred embodiment, the electron beam exposure machine uses a 100kV high voltage. In an optional implementation of the preferred embodiment, the concentration of the tetramethylammonium hydroxide (TMAH) developer is 20%±10%. In specific implementation, the exposure of the micro-nano fine pattern using an electron beam exposure machine and developing it with a tetramethylammonium hydroxide developer specifically includes: using a 100kV electron beam exposure with an exposure resolution of 0.1 nanometers; using a 20%±10% concentration of a tetramethylammonium hydroxide developer, and developing for 40 seconds by combining low-speed static development with high-speed dynamic liquid spray development.
[0043] Based on the above steps, this preferred embodiment is based on the characteristics of the wafer of thin film lithium niobate body material showing transparent color and poor conductivity, and the characteristics of electron beam negative photoresist HSQ. First, a layer of electron beam negative photoresist HSQ is coated on the surface of the wafer and a layer of metal aluminum is evaporated to enhance the conductivity of the wafer and reduce the transparency to appear white, so that EBL can be laser ranged. After EBL exposure, TMAH developer is used to dissolve and remove the metal aluminum and react with HSQ to form SiO2, providing a masking layer for subsequent etching processes. The metal aluminum above the electron beam photoresist not only has the effect of increasing conductivity and reducing transparency, but also avoids the cumbersome steps of metal etching after exposure and development below the photoresist.
[0044] Embodiment 2:
[0045] Based on the method provided in Example 1, this Example 2 provides a more specific implementation method to describe the method of the embodiment of the present invention in detail.
[0046] like Figure 2 As shown, the method of this embodiment includes the following steps:
[0047] Step 201: Electron beam negative photoresist HSQ is applied to a 4-inch thin film lithium niobate body material (LNOI). The speed of the photoresist is 2500 rpm, and the thickness of the photoresist is controlled at 700nm. In this step, 4 inches generally refers to the diameter of the surface circle. Specifically, 2 inches, 3 inches, and 4 inches can be selected. A circular piece or a rectangular piece can be exposed. In this step, the speed of the photoresist can be 2000-3000 rpm. This speed is for the final adjustment of the photoresist thickness. It should be noted that after the HSQ photoresist is developed, it will be converted into SiO2 as an etching mask layer. The etching depth of lithium niobate exceeds 250nm and SiO2 will be etched simultaneously during the etching process, so the HSQ needs a certain thickness; but if the HSQ is too thick, the coating speed will be high, and the exposure time will also increase. The increase in exposure time will further require equipment stability, so a suitable thickness is compromised, which is about 700nm.
[0048] Step 202: Use an evaporator to evaporate a 30nm thick aluminum film on the surface of the lithium niobate (LNOI) film after coating. It should be noted that if the aluminum film is too thin, the color is not obvious and still looks like transparent, and the thickness is not necessarily stable for the evaporation process; and if the aluminum film is too thick, it will increase the difficulty of stripping. The goal of this embodiment is to remove the metal layer before etching lithium niobate to save the metal etching step, so it is preferred to set a 30nm thick aluminum film.
[0049] Step 203: Use 100 kV electron beam exposure, and the exposure resolution is 0.1 nanometer. It should be noted that EBL equipment generally only has 50 or 100 kV high voltage, so this exposure only uses 100 kV, and the resolution of 0.1 nanometer is also determined by the equipment.
[0050] Step 204: Use a 20% concentration of tetramethylammonium hydroxide (TMAH) developer to develop for 40 seconds by combining low-speed static development with high-speed dynamic spray development. It should be noted that if the developer concentration is too low, it will be difficult to strip the metal, the development time will be too long, and the effect will be poor. If the concentration is too high, the development speed will be too fast and difficult to control. Therefore, in this embodiment, a TMAH developer with a concentration of about 20% is preferred, and the development time is controlled at about 40 seconds.
[0051] Step 205: After measuring the height of the pattern with a microscope, the subsequent ion beam etching of the body material can be carried out. This step is generally to first use a microscope to confirm that there is no metal residue, and then use a step profiler and an atomic force microscope to measure the depth of the SiO2 masking layer after exposure and development. Once the requirements are met, the subsequent ion beam etching operation can be carried out.
[0052] like Figure 3 As shown, it is a schematic diagram of the structure of the thin-film lithium niobate body material provided in this embodiment. The thin-film lithium niobate body material (LNOI) includes three layers, using a quartz substrate, on which is a layer of SiO2, and the surface is a lithium niobate film. The thickness of the quartz substrate is 550nm, the thickness of SiO2 is 2um, and the thickness of the lithium niobate film is 550nm. By the method in this embodiment, electron beam negative photoresist HSQ is applied on a 4-inch thin-film lithium niobate body material (LNOI). The speed of the photoresist machine is 2500 rpm, and the thickness of the photoresist is controlled at 700nm; then, a 30nm layer of metal aluminum (Al) film is evaporated on the surface of the thin-film lithium niobate body material (LNOI) after photoresistance. After this step is completed, the schematic diagram of the structure to be exposed by EBL is shown in the figure. Figure 4 Next, 100 kV electron beam exposure was used, and the exposure resolution was 0.1 nanometers. The EBL exposure schematic is shown in Figure 5Finally, a 20% concentration of tetramethylammonium hydroxide (TMAH) developer was used to develop for 40 seconds by combining low-speed static development with high-speed dynamic liquid spray development. During the development process, the metal aluminum film was corroded and removed by the developer and the HSQ in the exposed area was converted into amorphous SiO2, which served as a masking layer for subsequent etching processes. Finally, the schematic diagram of the wafer surface structure after TMAH solution development is shown in Figure 6 It should be noted that the layers shown in the figure are for reference only and do not represent the actual proportions of the layers.
[0053] In summary, the structure of the thin-film lithium niobate material (LNOI) of the present invention is a quartz substrate, on which is a layer of SiO2, and on the surface is a lithium niobate film. The bulk material structure is transparent and has poor conductivity. The transparent material cannot be laser-measured, which affects the EBL calibration and introduces serious splicing gaps. In response to this problem, the present invention first coats a layer of electron beam photoresist negative photoresist HSQ on the surface of the bulk material, and then evaporates a layer of metal aluminum thereon. After the metal is evaporated, the transparency is weakened and white appears, and the EBL can be laser-measured and calibrated. Then, an electron beam exposure machine (EBL) is used to expose micro-nano fine patterns, and tetramethylammonium hydroxide (TMAH) developer is used for development. The metal aluminum film can enhance the conductivity on the LNOI surface and improve the exposure accuracy and effect, and TMAH can corrode and remove the aluminum film during the development process, and convert HSQ into SiO2 as a masking layer for subsequent etching processes. The present invention overcomes the technical difficulties that EBL is not easy to expose transparent materials and materials with poor conductivity, avoids the complex metal etching process, and provides an exposure method for a thin-film lithium niobate modulator with a higher bandwidth.
[0054] Embodiment 3:
[0055] The embodiment of the present invention provides an exposure structure of a quartz substrate thin film lithium niobate body material, referring to Figure 5 The structure includes, from bottom to top, a quartz layer, a silicon dioxide layer, a lithium niobate thin film layer, an electron beam negative photoresist layer and a metal aluminum thin film layer, wherein an electron beam exposure area is arranged on the metal aluminum thin film layer; Figure 6 The structure after exposure using an electron beam exposure machine and development using a tetramethylammonium hydroxide developer includes, from bottom to top, a quartz layer, a silicon dioxide layer, a lithium niobate thin film layer, and a silicon dioxide masking layer, and the range of the silicon dioxide masking layer is the same as the range of the electron beam exposure area.
[0056] In this embodiment, a quartz layer, a silicon dioxide layer and a lithium niobate thin film layer constitute a thin film lithium niobate body material, wherein: the quartz layer is used as a substrate; the silicon dioxide layer is located on the quartz layer; and the lithium niobate thin film layer is located on the silicon dioxide layer. In an optional implementation of this preferred embodiment, the thickness of the quartz layer is 550±100um; the thickness of the silicon dioxide layer is 2±0.5um; and the thickness of the lithium niobate thin film layer is 550±150nm.
[0057] In this embodiment, the electron beam negative photoresist layer and the metal aluminum film layer are coatings added for exposing the thin film lithium niobate body material, wherein the electron beam negative photoresist HSQ can be applied to the thin film lithium niobate body material, the speed of the photoresist machine is 2500 rpm, and the photoresist thickness is controlled at 700±200nm. Then, a layer of 15-50nm metal aluminum film is sputtered on the surface of the thin film lithium niobate body material after photoresist by a sputtering machine. After completing this step, an exposure structure of the quartz substrate thin film lithium niobate body material is formed, that is, it includes a quartz layer, a silicon dioxide layer, a lithium niobate film layer, an electron beam negative photoresist layer and a metal aluminum film layer from bottom to top. The exposure structure is provided with an electron beam exposure area on the metal aluminum film layer, so as to expose micro-nano fine patterns by using an electron beam exposure machine, and develop with a tetramethylammonium hydroxide developer. Specifically, 100 kV electron beam exposure can be used, and the exposure resolution is 0.1 nanometers; a 20% ± 10% concentration of tetramethyl ammonium hydroxide developer is used, and the development is performed for 40 seconds by combining low-speed static development with high-speed dynamic liquid spray development. Finally, the electron beam negative resist layer and the metal aluminum film layer are eliminated by the developer, and the top silicon dioxide masking layer is formed.
[0058] In summary, the above technical scheme conceived by the present invention has the following beneficial effects compared with the prior art: the structure of the thin-film lithium niobate material (LNOI) of the present invention is a quartz substrate, on which is a layer of SiO2, and the surface is a thin-film lithium niobate. The bulk material structure is transparent and has poor conductivity. The transparent material cannot be laser-measured, which affects the EBL calibration and introduces serious splicing gaps. In response to this problem, the present invention first coats a layer of electron beam photoresist negative photoresist HSQ on the surface of the bulk material, and then evaporates a layer of metal aluminum thereon. After the metal is evaporated, the transparency is weakened and white appears, and the EBL can be laser-measured and calibrated. Then, an electron beam exposure machine (EBL) is used to expose micro-nano fine patterns, and tetramethylammonium hydroxide (TMAH) developer is used for development. The metal aluminum film can enhance the conductivity on the LNOI surface to improve the exposure accuracy and effect, and TMAH can corrode and remove the aluminum film during the development process, and convert HSQ into SiO2 as a masking layer for subsequent etching processes. The present invention overcomes the technical difficulty that transparent materials and materials with poor conductivity are not easily exposed by EBL, avoids the complex process of metal etching, and provides an exposure method for a thin-film lithium niobate modulator with a higher bandwidth.
[0059] A person skilled in the art may understand that all or part of the steps in the various methods of the embodiments may be completed by instructing related hardware through a program, and the program may be stored in a computer-readable storage medium, and the storage medium may include: a read-only memory (ROM), a random access memory (RAM), a disk or an optical disk, etc.
[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent replacement and improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.
Claims
1. An exposure method for a quartz substrate thin film lithium niobate material, characterized in that: include: Coating a layer of electron beam negative resist on the thin film lithium niobate body material; Evaporate a layer of metallic aluminum film on the electron beam negative resist; The micro-nano fine pattern was exposed by electron beam exposure machine and developed by tetramethylammonium hydroxide developer.
2. The exposure method of the quartz substrate thin film lithium niobate material according to claim 1, characterized in that: The thin film lithium niobate body material comprises a quartz layer, a silicon dioxide layer and a lithium niobate thin film layer; wherein: The quartz layer serves as a substrate; The silicon dioxide layer is located on the quartz layer; The lithium niobate thin film layer is located on the silicon dioxide layer.
3. The exposure method of the quartz substrate thin film lithium niobate material according to claim 2, characterized in that: The thickness of the quartz layer is 550±100um; the thickness of the silicon dioxide layer is 2±0.5um; and the thickness of the lithium niobate thin film layer is 550±150nm.
4. The exposure method of the quartz substrate thin film lithium niobate material according to claim 1, characterized in that: The electron beam negative resist includes HSQ, and the thickness of the electron beam negative resist is 700±200 nm.
5. The exposure method of the quartz substrate thin film lithium niobate material according to claim 1, characterized in that: The thickness of the metal aluminum film is 15-50nm.
6. The exposure method of the quartz substrate thin film lithium niobate material according to claim 1, characterized in that: The electron beam exposure machine adopts 100kV high voltage; the concentration of the tetramethylammonium hydroxide developer is 20%±10%.
7. The exposure method of the quartz substrate thin film lithium niobate material according to claim 1, characterized in that: The step of coating a layer of electron beam negative resist on the thin film lithium niobate material specifically comprises: Electron beam negative photoresist HSQ was applied to 2-inch to 4-inch thin film lithium niobate material. The rotation speed of the photoresist was 2500±500 rpm and the photoresist thickness was controlled at 700±200nm.
8. The exposure method of the quartz substrate thin film lithium niobate material according to claim 7, characterized in that: The evaporation of a metal aluminum film on the electron beam negative resist specifically includes: A 15-50nm thick metal aluminum film is evaporated on the surface of the lithium niobate thin film material after the coating by an evaporator.
9. The exposure method of the quartz substrate thin film lithium niobate material according to claim 8, characterized in that: The method of using an electron beam exposure machine to expose micro-nano fine patterns and using a tetramethylammonium hydroxide developer to develop the patterns specifically includes: 100kV electron beam exposure was used, and the exposure resolution was 0.1 nanometer; A 20%±10% concentration of tetramethylammonium hydroxide developer is used, and development is performed for 40±5 seconds by combining low-speed static development with high-speed dynamic spray development.
10. An exposure structure of a quartz substrate thin film lithium niobate material, characterized in that: The invention comprises, from bottom to top, a quartz layer, a silicon dioxide layer, a lithium niobate film layer, an electron beam negative resist layer and a metal aluminum film layer. An electron beam exposure area is arranged on the metal aluminum film layer. The structure after exposure by an electron beam exposure machine and development with a tetramethylammonium hydroxide developer comprises, from bottom to top, a quartz layer, a silicon dioxide layer, a lithium niobate film layer and a silicon dioxide masking layer. The range of the silicon dioxide masking layer is the same as that of the electron beam exposure area.